1980
DOI: 10.1002/1097-0142(19800101)45:1<30::aid-cncr2820450107>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized combined modality trial in small cell carcinoma of the lung comparison of combination chemotherapy-radiation therapy versus cyclophosphamide-radiation therapy effects of maintenance chemotherapy and prophylactic whole brain irradiation

Abstract: A randomized trial of combined modality therapy employing combination chemotherapy (cyclophosphamide (CTX) and methotrexate (MTX), CTX, MTX and Vincristine (VCR) and CTX, VCR and high-dose MTX with citrovorum rescue) and radiation therapy was compared to cyclophosphamide and radiation therapy in 258 patients with pulmonary small cell carcinoma. Patients were also rendomized: 1) to determine the effects of prophylactic whole brain irradiation; and 2) to establish the effects of maintenance chemotherapy. Surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
1
1

Year Published

1980
1980
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(32 citation statements)
references
References 0 publications
5
25
1
1
Order By: Relevance
“…15 However, the metaanalysis included various trials and often insufficient systemic chemotherapy regimens, different PCI techniques, and a mixed population of patients with limited and extensive disease. [12][13][14][15] Therefore, Kotalik et al 18 found there was insufficient evidence to make a definitive recommendation in terms of the total dose, fractionation, indication, and timing of PCI according to this metaanalysis. In the current study, 16.9% of patients had brain metastasis as a first site of failure, which is consistent with previous reports of 4 -24%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15 However, the metaanalysis included various trials and often insufficient systemic chemotherapy regimens, different PCI techniques, and a mixed population of patients with limited and extensive disease. [12][13][14][15] Therefore, Kotalik et al 18 found there was insufficient evidence to make a definitive recommendation in terms of the total dose, fractionation, indication, and timing of PCI according to this metaanalysis. In the current study, 16.9% of patients had brain metastasis as a first site of failure, which is consistent with previous reports of 4 -24%.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, 16.9% of patients had brain metastasis as a first site of failure, which is consistent with previous reports of 4 -24%. 6,[12][13][14] The salvage treatment for brain metastasis after PCI would be restricted by the number of brain metastases, patient condition, and previous irradiation. To our knowledge, no report has described the predictive or prognostic factors for outcomes after PCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Majority of the nine published randomised trials confirm that PCI in doses of about 30 Gy reduces significantly the incidence of brain relapse (Jackson, 1985;Cox, 1978;Beiler, 1979;Maurer, 1980;Hansen, 1980;Eagan, 1981;Katsenis, 1982;Seydel, 1983). There is regrettably only one published trial in patients with a complete response to chemotherapy (Aroney, 1983).…”
mentioning
confidence: 99%